THE RELATIONSHIP OF INCREASING BLOOD LACTIC AND LEFT VENTRICLE EJECTION FRACTION (LVEF) IN ST ELEVASI MIOKARD INFARK (STEMI) PATIENTS IN ADAM MALIK HOSPITAL MEDAN, 2019 - Henry Sibarani, Zainal Safri & Rahmat Isnanta (International Journal of Research Science and Management, 2019)
Introduction: Cardiovascular disease is the leading cause of death in the world. Lactate is produced by most tissues in the human body, with the highest production levels found in muscles. In anaerobic conditions, lactate is the final product of glycolysis and gluconeogenesis Knowing early heart attack is very important. Lactic acid will increase and LVEF will decrease during a heart attack. Aim: Toinvestigatethe relationship of increasing blood lactic acid levels with a decrease in the Left Ventricular Ejection Fraction (LVEF) of ST-Elevation Myocardial Infarction (STEMI) patients. Methods: A prospective observational study was conducted at the Haji Adam Malik General Hospital in Medan from June 2018 to March 2019 with total sample are 45STEMI patients. Patients performed Lactate and Echocardiography examinations on the first day. Data analysis using SPSS 22nd. Result: 50 STEMI patients were tested lactic acid levels : group ≥ 2.5 mmol / l were 18 patients (40%), group <2.5 mmol / l were 27 patients (60%). Echocardiography examination was divided into LVEF ≥ 50% were 26 patients (58%) and LVEF <50% were 19 patients (42%)..It was found that there were a significant relationship between the increasing lactic acid levels and a decrease in LVEF in STEMI patients( p = 0.03) and OR = 9.1. Conclusion: Increasing lactic acid levelsis significantly related to decrease in LVEF.